3(p+2)=3(2p+4)+9

Simple and best practice solution for 3(p+2)=3(2p+4)+9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(p+2)=3(2p+4)+9 equation:


Simplifying
3(p + 2) = 3(2p + 4) + 9

Reorder the terms:
3(2 + p) = 3(2p + 4) + 9
(2 * 3 + p * 3) = 3(2p + 4) + 9
(6 + 3p) = 3(2p + 4) + 9

Reorder the terms:
6 + 3p = 3(4 + 2p) + 9
6 + 3p = (4 * 3 + 2p * 3) + 9
6 + 3p = (12 + 6p) + 9

Reorder the terms:
6 + 3p = 12 + 9 + 6p

Combine like terms: 12 + 9 = 21
6 + 3p = 21 + 6p

Solving
6 + 3p = 21 + 6p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-6p' to each side of the equation.
6 + 3p + -6p = 21 + 6p + -6p

Combine like terms: 3p + -6p = -3p
6 + -3p = 21 + 6p + -6p

Combine like terms: 6p + -6p = 0
6 + -3p = 21 + 0
6 + -3p = 21

Add '-6' to each side of the equation.
6 + -6 + -3p = 21 + -6

Combine like terms: 6 + -6 = 0
0 + -3p = 21 + -6
-3p = 21 + -6

Combine like terms: 21 + -6 = 15
-3p = 15

Divide each side by '-3'.
p = -5

Simplifying
p = -5

See similar equations:

| -3/4x=-9 | | 3(v-8)+-9=-6 | | 1-c=-7 | | -6x-5y=-27 | | 4X+5=2(-2X+4) | | -24=5g+15 | | -7m+9=26-2m | | 2(X+5)+6X=-27 | | -3x^2+18x=34 | | 3(h+8)=-18 | | 4X+5=-4X+6 | | 5x-(6x+6)=3x-50 | | 2(d-10)+2=-8 | | y+10x=8 | | 2(y+1)-15=5 | | 24x^4y+21x^3= | | 10(5+W)=-3(W+5) | | 2-4x=5x+20 | | 2030+5x=-15 | | -15k-7k+-10=12 | | 1/38=2.25/x | | 7/3-7i | | 5x-31=x+5 | | 9x+27x^2= | | -12n+16n+-19=-13 | | -3a+8b+61=0 | | 27.00/2.25 | | 1/38=5.5/x | | 2(c-8)+-6=8 | | -2x+3(x-3)=-13 | | 11=-5x+21 | | a^4+8=11 |

Equations solver categories